Needs assessment and impact of COVID-19 on pharmacy professionals in 31 commonwealth countries - Diane Ashiru-Oredope; Amy Hai Yan Chan; Omotayo Olaoye; Victoria Rutter; Zaheer-; The C. P. A. COVID-19 Action Team (Taylor & Francis Group, 2020)
Background The declaration of COVID-19 a pandemic by the World Health Organization on 11 March 2020 marked the beginning of a global health crisis of an unprecedented nature and scale. The approach taken by countries across the world varied widely, however, the delivery of frontline healthcare was consistently recognised as being central to the pandemic response. This study aimed to identify and explore the issues currently facing pharmacy teams across Commonwealth countries during the COVID-19 pandemic. The study also evaluates pharmacy professionals' understanding of key knowledge areas from the COVID-19 webinar hosted by the Commonwealth Pharmacists' Association (CPA). Method A quantitative survey-based approach was adopted, using a 32-item questionnaire developed from the literature on pharmacy and pandemic response. The survey was hosted on Survey Monkey and pilot tested. The final survey was disseminated by CPA member organisations. A 6-item online questionnaire was sent via email to all attendees of CPA's COVID-19 webinar. Descriptive statistics on frequency distributions and percentages were used to analyse the responses. Data were analysed using Microsoft® Excel (2010). Results There were 545 responses from pharmacy professionals across 31/54 Commonwealth countries in Africa, Asia, the Americas, Europe and the Pacific. Majority of the respondents reported being at least somewhat worried (90%) and more than 65% were very worried or extremely about the impact of COVID-19 on them personally and professionally. Nearly two-thirds of respondents stated finding it somewhat difficult or very difficult to work effectively during the pandemic. Challenges mostly faced by pharmacy professionals working remotely included; general anxiety about the impact of COVID-19 on their lives (12%), and difficulties in communicating with their co-workers (12%). Most pharmacy professionals had not previously been actively involved in a global health emergency (82%) nor obtained training on global/public health emergency preparedness (62%). Between 45 and 97% of the COVID-19 webinar attendees provided the correct answers to post-webinar questions, suggesting some improvement in knowledge. Conclusion Our study confirms pharmacy professionals' concerns about practice during a pandemic and provides preliminary data on the challenges and learning needs of the profession. The CPA has since acted on these findings, providing ongoing opportunities to develop and refine resources for the profession as the pandemic evolves. Pharmacy professionals have also demonstrated improved knowledge on the management of COVID-19 and resources available for professionals.